The performance management system used by Celestica Electronics (M) Sdn Bhd / Siti Nur Fairuzah Mohd Shariffuddin - Mohd Shariffuddin, Siti Nur Fairuzah (2010)
This case study aims at examining the Performance Management System used by Celestica Electronics (M). Performance Management is very crucial for the success of a company because an effective performance management system is able to help both employees and the organization to accomplish their goals. In terms of the Performance Management System incorporated by Celestica, they use a system called Performance Development Planning (PDP). But there were weaknesses in the system that made employees become unsatisfied with the process and resorted to them leaving the company. Driving this effort is the theory presented by scholars regarding the Performance Management Model which includes Performance Planning, Ongoing Coaching, Multiple Sources of Feedback and Performance Review. Thus the purpose of this study is to explain the process of Performance Management carried out by Celestica and compare it to the Performance Management Model provided by theory. The comparison is made by conducting a gap analysis between theory, company procedure and the actual practice of performance management system by the company. Through the analysis it was found that there were not many gaps between theory and the company procedure of performance management. The underlying problem found was that the implementation of the system or the actual practice deviates from the procedure of Performance Management provided by the company. Among the recommendations for the company is that they should appoint a person to review or audit the PDP process and create a communication culture in the company.